Abbreviation in the works of the potter Shenyar Abdullah (Al-Academy, 2025)
The art of ceramics is one of the main pillars of contemporary Iraqi plastic art, whose contemporary beginnings were represented by the emergence of its Greek teacher (Valentinos) and then the potters Saad Shaker, Akram Naji, Shenyar Abdullah, Jawad Al-Zubaidi, Abdul-Kadhim Ghanem, as well as Maher Al-Samarrai, Tariq Ibrahim, Qasim Nayef, Angham Saadoun, Ahmed Al-Hindawi, Zainab Al-Bayati, Ahmed Jaafar, and others. Their artistic styles developed through the abandonment of the realistic style by their artists and their persistent search to create a contemporary Iraqi ceramic art characterized by a contemporary style and techniques. Among these artists is the potter Shenyar Abdullah, whose ceramic production is characterized by a severe reduction of ceramic shapes and formations in their general construction and distinctive colours. Hence, the importance of our research in a study that reveals the nature of reduction in his ceramic productions and the characteristics of this reduction emerges, as Shenyar Abdullah is one of the Iraqi potters whose productions are characterized by transformations at the level of ceramic production and its formal reductions, as Shenyar Abdullah relied in his innovation on reduced ceramic shapes and formations, as they appear as if they are forms that have no origin and no counterpart, in forms that are characterized by their compositional, aesthetic and creative uniqueness, as he is unique in his reduced productions due to those formations and his distinctive technical and aesthetic ability. The research consists of several chapters, the first of which includes the research problem, its importance, the need for it, its objectives, and the definition of its terms, while the second chapter represents the theoretical framework and includes two studies: the first is reduction and artistic vision, and the second is the contemporary Iraqi ceramics movement. The third chapter came with an analysis of the research sample models, while the fourth chapter represented the results and conclusions.